Overview about the recovery of soluble whey proteins - García Casas, Victoria (Revista Universidad de Guayaquil, 2015)
The whey milk is a product of the cheese industry, rich in nutrients of high biological value, it is being used by many developed countries and in process of development in different industrial processes. Proteins are substances that are presented in vegetable and animal cells, they form molecules information, as several authors quote that they are macronutrients that comply more functions in living creatures, such as meta bolic, structural and regulatory, this is reason why they are considered as complex organic compounds Meanwhile, the serum proteins represent the 25% of total milk protein, they are formed by holoproteins and glycoproteins, also known as soluble proteins, these proteins are so important because of the lead role they play to the food industry due to their functional properties that are considered as conducive to be ad ded as an ingredient in miscellaneous food products. Together these characteristics have encouraged great efforts in research and development of new technologies in order to enhance recovery of this dairy product.